Changing The Mindset of The Indigenous Dayak Community in West Kalimantan Towards Indigenous Forests as A Result of Palm Oil Plantations - Baging, Pitalis Mawardi (Yayasan Sembilan Pemuda Indonesia, 2023)
Since the opening of oil palm plantations in 1980 in West Kalimantan, which since 1982 has been managed under the People’s Nucleus Plantation (PIR-Bun) pattern, slowly but surely changing the mindset of indigenous Dayak people towards jungle forests or ulayat lands. Its influence is increasingly felt in the behavior and social life of the local community. The Dayak community has experienced a change in their “world view” of the forest. Those who have been friendly with nature since ancient times and uphold traditional principles, now in their lives, on the one hand, are leaving their ancestral traditions and following the trend of oil palm plantations, but on the other hand, their lives are increasingly cornered by the existence of oil palm plantations. The permissive attitude and pragmatism of those in power have resulted in a change in the “world view” of the local community. They no longer respect nature or forests as “sacred lands”. Society is also increasingly pragmatic, hedonic and consumptive. Local customs and wisdom in the form of family values, mutual cooperation, loyalty to the community, humility, sincerity, respect for nature and each other are increasingly fading. The jungle forest and “tembawang forest” as customary rights have mostly been just stories.